AVIOBRIDGE MAINTENANCE MANAGEMENT: A SOLUTION FOR CABIN CURTAIN DAMAGE - Ingelda Gabrella; Imam Haryadi; Annisa Baby Callista (Journal of Airport Engineering Technology (JAET), 2023)
This research raises the problem in one of the traction equipment after the absence during covid-19 with evidence that an occurrence causing trouble with the curtain results from a lack of monitoring and maintenance. As a result, the curtain gets out of the way of the cabin, which causes the following impacts passenger may be trapped, unstable curtain movement rotation, and the sound of the curtain becomes harsh. This research aims to prevent further damage to the cabin curtain, considering that aviobridge is one of the supporting flight operations at the airport. This research uses an exploratory study using literature, observations, and interviews. This research indicates that maintenance to aviobridge does not conduct appropriately during the pandemic causing problems for the aviobridge. The result is expected that maintenance will be carried out according to applicate standard operating procedures such as lubricants between the curtains using lubricants such lubrication simultaneously with the movement of the cabin rotation to the right and left, checking the roller curtains at the top and bottom using shock lock 32, and adjusting the gear up and down if already loose. Intensive preventive maintenance is the key to establishing any facilities and the sign of a good quality of production in the industry. The researcher calculated the Mean Time Between Failure (MTBF) and Mean Time To Repair (MTTR) with the sample to the parking stand N06 and proposed that the organization obeys the applicable standard operating procedures for maintenance.